2019
DOI: 10.1186/s12885-019-5584-6
|View full text |Cite
|
Sign up to set email alerts
|

Targeted capture-based NGS is superior to multiplex PCR-based NGS for hereditary BRCA1 and BRCA2 gene analysis in FFPE tumor samples

Abstract: Background: With the introduction of Olaparib treatment for BRCA-deficient recurrent ovarian cancer, testing for somatic and/or germline mutations in BRCA1/2 genes in tumor tissues became essential for treatment decisions. In most cases only formalin-fixed paraffin-embedded (FFPE) samples, containing fragmented and chemically modified DNA of minor quality, are available. Thus, multiplex PCR-based sequencing is most commonly applied in routine molecular testing, which is predominantly focused on the identificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 39 publications
3
23
0
1
Order By: Relevance
“…The fact that the distribution of somatic mutations was consistent with other Chinese studies (36,48) and with a Polish study using FFPE tissues from HGSC patients (52) could guarantee the quality of our sample preparation. It was suggested that an adjusted targeted capture-based enrichment protocol was superior to commonly applied multiplex PCRbased protocols for reliable BRCA1/2 variant detection, including CNV detection, using FFPE tumor samples (53). As previously reported, the prevalence of BRCA1/2 mutations in patients with peritoneal carcinoma or fallopian tube carcinoma is comparable to that in EOC patients (54).…”
Section: Discussionmentioning
confidence: 94%
“…The fact that the distribution of somatic mutations was consistent with other Chinese studies (36,48) and with a Polish study using FFPE tissues from HGSC patients (52) could guarantee the quality of our sample preparation. It was suggested that an adjusted targeted capture-based enrichment protocol was superior to commonly applied multiplex PCRbased protocols for reliable BRCA1/2 variant detection, including CNV detection, using FFPE tumor samples (53). As previously reported, the prevalence of BRCA1/2 mutations in patients with peritoneal carcinoma or fallopian tube carcinoma is comparable to that in EOC patients (54).…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, the enrichment-based design can be adapted to be used, not only for high-quality DNA, but also for low-quality and fragmented DNA from paraffin-embedded (FFPE) tumor tissues. [26]…”
Section: Resultsmentioning
confidence: 99%
“…Copy number variants (CNVs), for instance, are typically not detected by NGS-based variant calling [26]. We therefore applied a CNV detection approach based on the sequencing data generated by our custom panel in order to complement single nucleotide variant (SNV) detection from both cryo-conserved tumor samples and paraffin embedded tissues.…”
Section: Discussionmentioning
confidence: 99%
“…However, comprehensive analysis by NGS enables the sequencing results of many amplicons with a short base pair length at the same time, demonstrating that genetic analysis can also be performed on DNA extracted from FFPE tissues, and making it easier to introduce genetic analysis into pathological diagnosis. [21][22][23][24][25] Despite FFPE use, there is a debate of whether FFPE applicable to genetic analysis can maintain satisfactory quality by avoiding damage to nucleic acids, due to formalin fixation and degradation of nucleic acids based on long-term storage in a paraffin block. Visual fragmentation confirmation by electrophoresis and Ct value by quantitative PCR are used as quality parameters for nucleic acids.…”
Section: Introductionmentioning
confidence: 99%